2013
DOI: 10.5430/jst.v4n1p11
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lesions to the liver: Surgical indications and techniques

Abstract: Background: Although there is an established agreement on the advantage of liver resection for metastatic colorectal and neuroendocrine tumours, the role of hepatic surgery in patients with liver metastases from non-colorectal and non-neuroendocrine carcinoma is not well defined. In recent years, despite the poor results, liver metastases suitable for surgery have been treated with resection. The results reported in recent studies support a developing trend toward surgery in this setting. Also, as there are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 102 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Several studies have shown 5-year survival rates of up to 86% in R0 resection for both primary and secondary sites. Cytoreduction is useful as a palliative approach (57). RFA is shown to relieve symptoms in 60% of the cases with local disease control in 80%, although the length of response is short (57).…”
Section: Non Colorectal Liver Metastasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown 5-year survival rates of up to 86% in R0 resection for both primary and secondary sites. Cytoreduction is useful as a palliative approach (57). RFA is shown to relieve symptoms in 60% of the cases with local disease control in 80%, although the length of response is short (57).…”
Section: Non Colorectal Liver Metastasesmentioning
confidence: 99%
“…Cytoreduction is useful as a palliative approach (57). RFA is shown to relieve symptoms in 60% of the cases with local disease control in 80%, although the length of response is short (57). Transarterial chemoembolisation (TACE), also has a short duration of response (57).…”
Section: Non Colorectal Liver Metastasesmentioning
confidence: 99%
See 1 more Smart Citation